Hero-based interventions to promote health and education in young people: A scoping review - Kevin O'Malley; Elaine L. Kinsella; Eric R. Igou; Alison English; Jennifer McMahon (SSM - Mental Health)
Objective: Programs using heroes to promote positive health and educational outcomes for children and adolescents have been increasingly implemented. However, a comprehensive review of such interventions is lacking. This scoping review maps the existing empirical literature on hero-based interventions. Method: A systematic search of databases including CINAHL, ERIC, MEDLINE, and others (final search February 2025), covering all years up to January 2025 identified peer-reviewed studies in English on hero-based interventions targeting health or educational outcomes in children and adolescents. Exclusions in-cluded non-English papers, those lacking empirical results, focusing on adults, or classified as grey literature. Data on study characteristics were extracted and analyzed using Arksey and O'Malley's (2005) framework. Results: From 134 screened articles, 39 met the inclusion criteria, identifying 11 distinct programs targeting diverse populations across regions such as the U.S., U.K., India, Turkey, and Japan. These programs, im-plemented in both educational and clinical settings, addressed physical and mental health, education, social skills, and trauma recovery. The review assessed empirical support for these programs, noting variability in evidence strength, and highlighted their adaptability across different cultural contexts. Conclusions: Hero-based interventions show promise in supporting youth across various outcomes, though no universal approach exists. Tailoring interventions to the specific cultural and contextual needs of young people is essential. Future research should focus on refining these methods, matching heroes to participants, and independent replication.